Sensing and Shaping Emerging Conflicts: Report of a Workshop by the National Academy of Engineering and United States Institute of Peace Roundtable on Technology, Science, and Peacebuilding - National Academy of Engineering
Technology has revolutionized many aspects of modern life, from how businesses operate, to how people get information, to how countries wage war. Certain technologies in particular, including not only cell phones and the Internet but also satellites, drones, and sensors of various kinds, are transforming the work of mitigating conflict and building peaceful societies. Rapid increases in the capabilities and availability of digital technologies have put powerful communications devices in the hands of most of the world's population. These technologies enable one-to-one and one-to-many flows of information, connecting people in conflict settings to individuals and groups outside those settings and, conversely, linking humanitarian organizations to people threatened by violence. Communications within groups have also intensified and diversified as the group members use new technologies to exchange text, images, video, and audio. Monitoring and analysis of the flow and content of this information can yield insights into how violence can be prevented or mitigated. In this way technologies and the resulting information can be used to detect and analyze, or sense, impending conflict or developments in ongoing conflict. On October 11, 2012, the National Academy of Engineering (NAE) and the United States Institute of Peace (USIP) held a workshop in Washington, DC, to identify \

Technically Speaking: Why All Americans Need to Know More About Technology - National Academy of Engineering; National Research Council (The National Academies Press, 2002)
Cell phones . . . airbags . . . genetically modified food . . . the Internet. These are all emblems of modern life. You might ask what we would do without them. But an even more interesting question might be what would we do if we had to actually explain how they worked? The United States is riding a whirlwind of technological change. To be sure, there have been periods, such as the late 1800s, when new inventions appeared in society at a comparable rate. But the pace of change today, and its social, economic, and other impacts, are as significant and far reaching as at any other time in history. And it seems that the faster we embrace new technologies, the less we2019re able to understand them. What is the long-term effect of this galloping technological revolution? In today2019s new world, it is nothing less than a matter of responsible citizenship to grasp the nature and implications of technology. Technically Speaking provides a blueprint for bringing us all up to speed on the role of technology in our society, including understanding such distinctions as technology versus science and technological literacy versus technical competence. It clearly and decisively explains what it means to be a technologically-literate citizen. The book goes on to explore the context of technological literacy2014the social, historical, political, and educational environments. This readable overview highlights specific issues of concern: the state of technological studies in K-12 schools, the reach of the Internet into our homes and lives, and the crucial role of technology in today2019s economy and workforce. Three case studies of current issues2014car airbags, genetically modified foods, and the California energy crisis2014illustrate why ordinary citizens need to understand technology to make responsible decisions. This fascinating book from the National Academy of Engineering is enjoyable to read and filled with contemporary examples. It will be important to anyone interested in understanding how the world around them works.

Telecommunications Research and Engineering at the Communications Technology Laboratory of the Department of Commerce: Meeting the Nation's Telecommunications Needs - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
The Department of Commerce operates two telecommunications research laboratories located at the Department of Commerce's Boulder, Colorado, campus: the National Telecommunications and Information Administration's (NTIA's) Institute for Telecommunications Sciences (ITS) and the National Institute of Standards and Technology's (NIST's) Communications Technology Laboratory (CTL). CTL develops appropriate measurements and standards to enable interoperable public safety communications, effective and efficient spectrum use and sharing, and advanced communication technologies. CTL is a newly organized laboratory within NIST, formed mid-2014. As it is new and its planned work represents a departure from that carried out by the elements of which it was composed, this study focuses on its available resources and future plans rather than past work. The Boulder telecommunications laboratories currently play an important role in the economic vitality of the country and can play an even greater role given the importance of access to spectrum and spectrum sharing to the wireless networking and mobile cellular industries. Research advances are needed to ensure the continued evolution and enhancement of the connected world the public has come to expect.

Telecommunications Research and Engineering at the Institute for Telecommunication Sciences of the Department of Commerce: Meeting the Nation's Telecommunications Needs - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
The Department of Commerce operates two telecommunications research laboratories located at the Department of Commerce's Boulder, Colorado, campus: the National Telecommunications and Information Administration's (NTIA's) Institute for Telecommunications Sciences (ITS) and the National Institute of Standards and Technology's (NIST's) Communications Technology Laboratory (CTL). ITS serves as a principal federal resource for solving the telecommunications concerns of federal agencies, state and local governments, private corporations and associations, standards bodies, and international organizations. ITS could provide an essential service to the nation by being a principal provider of instrumentation and spectrum measurement services; however, the inter-related shortages of funding, staff, and a coherent strategy limits its ability to fully function as a research laboratory. This report examines the institute's performance, resources, and capabilities and the extent to which these meet customer needs. The Boulder telecommunications laboratories currently play an important role in the economic vitality of the country and can play an even greater role given the importance of access to spectrum and spectrum sharing to the wireless networking and mobile cellular industries. Research advances are needed to ensure the continued evolution and enhancement of the connected world the public has come to expect.

Is That Real?: Identification and Assessment of the Counterfeiting Threat for U.S. Banknotes - National Research Council (The National Academies Press, 2006)
A key mission of the Bureau of Engraving and Printing of the Department of the Treasury is the design and printing of U.S. banknotes. The BEP is responsible for producing easily recognizable currency that is difficult to counterfeit. In recent years, the bureau has recognized the modern information technology could lead to entirely new types of counterfeiting threats, and it has requested a number of studies by the NRC to assess these evolving threats. In this new request, the BEP asked the NRC to identify and evaluate significant emerging counterfeiting threats and to assess technologically feasible counterfeit-deterrent features for potential use in new designs. This first report provides an assessment of emerging threats including a wide range of digital imaging and printing techniques. It also presents an analysis of a systems approach to the counterfeiting threat. The second report will offer an evaluation of new banknote features to address these threats.

Persistent Forecasting of Disruptive Technologies—Report 2 - National Research Council
The term \

Implications of Emerging Micro- and Nanotechnologies - National Research Council (The National Academies Press, 2002)
Expansion of micro-technology applications and rapid advances in nano-science have generated considerable interest by the Air Force in how these developments will affect the nature of warfare and how it could exploit these trends. The report notes four principal themes emerging from the current technological trends: increased information capability, miniaturization, new materials, and increased functionality. Recommendations about Air Force roles in micro- and nanotechnology research are presented including those areas in which the Air Force should take the lead. The report also provides a number of technical and policy findings and recommendations that are critical for effective development of the Air Force2019s micro- and nano-science and technology program

Persistent Forecasting of Disruptive Technologies - National Research Council (The National Academies Press, 2010)
Technological innovations are key causal agents of surprise and disruption. In the recent past, the United States military has encountered unexpected challenges in the battlefield due in part to the adversary's incorporation of technologies not traditionally associated with weaponry. Recognizing the need to broaden the scope of current technology forecasting efforts, the Office of the Director, Defense Research and Engineering (DDR&E) and the Defense Intelligence Agency (DIA) tasked the Committee for Forecasting Future Disruptive Technologies with providing guidance and insight on how to build a persistent forecasting system to predict, analyze, and reduce the impact of the most dramatically disruptive technologies. The first of two reports, this volume analyzes existing forecasting methods and processes. It then outlines the necessary characteristics of a comprehensive forecasting system that integrates data from diverse sources to identify potentially game-changing technological innovations and facilitates informed decision making by policymakers. The committee's goal was to help the reader understand current forecasting methodologies, the nature of disruptive technologies and the characteristics of a persistent forecasting system for disruptive technology. Persistent Forecasting of Disruptive Technologies is a useful text for the Department of Defense, Homeland Security, the Intelligence community and other defense agencies across the nation.

Globalization of Materials R&D: Time for a National Strategy - National Research Council (The National Academies Press, 2005)
Materials Science and Engineering (MSE) R&D is spreading globally at an accelerating rate. As a result, the relative U.S. position in a number of MSE subfields is in a state of flux. To understand better this trend and its implications for the U.S. economy and national security, the Department of Defense (DOD) asked the NRC to assess the status and impacts of the global spread of MSE R&D. This report presents a discussion of drivers affecting U.S. companies' decisions about location of MSE R&D, an analysis of impacts on the U.S. economy and national security, and recommendations to ensure continued U.S. access to critical MSE R&D.

Adding Value to the Facility Acquisition Process: Best Practices for Reviewing Facility Designs - Ralph S. Spillinger (The National Academies Press, 2000)
The federal government, like private corporations and other organizations, acquires buildings and other facilities to support specific functions and missions and the general conduct of its business. The federal government is, in fact, the nation's largest owner of buildings and spends more than 20 billion per year for facility design and construction. Adding Value to the Facility Acquisition Processidentifies a range of best practices and technologies that can be used by federal agencies and other owners to provide adequate management and oversight of design reviews throughout the facility acquisition process.

New Directions for Chemical Engineering - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Over the past century, the work of chemical engineers has helped transform societies and the lives of individuals, from the synthetic fertilizers that helped feed the world to the development of novel materials used in fuels, electronics, medical devices, and other products. Chemical engineers' ability to apply systems-level thinking from molecular to manufacturing scales uniquely positions them to address today2019s most pressing problems, including climate change and the overuse of resources by a growing population. New Directions for Chemical Engineering details a vision to guide chemical engineering research, innovation, and education over the next few decades. This report calls for new investments in U.S. chemical engineering and the interdisciplinary, cross-sector collaborations necessary to advance the societal goals of transitioning to a low-carbon energy system, ensuring our production and use of food and water is sustainable, developing medical advances and engineering solutions to health equity, and manufacturing with less waste and pollution. The report also calls for changes in chemical engineering education to ensure the next generation of chemical engineers is more diverse and equipped with the skills necessary to address the challenges ahead.

Understanding the Educational and Career Pathways of Engineers - National Academy of Engineering (The National Academies Press, 2018)
Engineering skills and knowledge are foundational to technological innovation and development that drive long-term economic growth and help solve societal challenges. Therefore, to ensure national competitiveness and quality of life it is important to understand and to continuously adapt and improve the educational and career pathways of engineers in the United States. To gather this understanding it is necessary to study the people with the engineering skills and knowledge as well as the evolving system of institutions, policies, markets, people, and other resources that together prepare, deploy, and replenish the nation's engineering workforce. This report explores the characteristics and career choices of engineering graduates, particularly those with a BS or MS degree, who constitute the vast majority of degreed engineers, as well as the characteristics of those with non-engineering degrees who are employed as engineers in the United States. It provides insight into their educational and career pathways and related decision making, the forces that influence their decisions, and the implications for major elements of engineering education-to-workforce pathways.

Frontiers of Materials Research: A Decadal Survey - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Modern materials science builds on knowledge from physics, chemistry, biology, mathematics, computer and data science, and engineering sciences to enable us to understand, control, and expand the material world. Although it is anchored in inquiry-based fundamental science, materials research is strongly focused on discovering and producing reliable and economically viable materials, from super alloys to polymer composites, that are used in a vast array of products essential to today's societies and economies. Frontiers of Materials Research: A Decadal Survey is aimed at documenting the status and promising future directions of materials research in the United States in the context of similar efforts worldwide. This third decadal survey in materials research reviews the progress and achievements in materials research and changes in the materials research landscape over the last decade; research opportunities for investment for the period 2020-2030; impacts that materials research has had and is expected to have on emerging technologies, national needs, and science; and challenges the enterprise may face over the next decade.

The National Science Foundation's Materials Research Science and Engineering Centers Program: Looking Back, Moving Forward - National Research Council (The National Academies Press, 2007)

Advanced Research Instrumentation and Facilities - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2006)

NSF Efforts to Achieve the Nation's Vision for the Materials Genome Initiative: Designing Materials to Revolutionize and Engineer Our Future (DMREF) - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The Materials Genome Initiative (MGI) was launched in 2011 by the White House Office of Science and Technology Policy to help accelerate the design, discovery, development and deployment of advanced materials and to reduce costs through the integration of advanced computation and data management with experimental synthesis and characterization. A broad range of federal agencies - including the National Science Foundation (NSF), the Department of Energy, and the Department of Defense - are part of the MGI effort and have invested more than 1 billion in resources and infrastructure accumulative since the start. The efforts of NSF have been focused largely within the Designing Materials to Revolutionize and Engineer Our Future (DMREF) program, which supports the development of fundamental science, computational and experimental tools for generating and managing data, and workforce that enable industry and other government agencies to develop and deploy materials that meet societal needs and national priorities. At the request of NSF, this report evaluates the goals, progress, and scientific accomplishments of the DMREF program within the context of similar efforts both within the United States and abroad. The recommendations of this report will assist NSF as it continues to increase its engagement with industry and federal agencies to transition the results from fundamental science efforts to reach the MGI goal of deploying advanced materials at least twice as fast as possible today, at a fraction of the cost that meet national priorities.

A Path to the Next Generation of U.S. Banknotes: Keeping Them Real - National Research Council (The National Academies Press, 2007)
The rapid pace at which digital printing is advancing is posing a very serious challenge to the U.S. Department of the Treasury2019s Bureau of Printing (BEP). The BEP needs to stay ahead of the evolving counterfeiting threats to U.S. currency. To help meet that challenge, A Path to the Next Generation of U.S. Banknotes provides an assessment of technologies and methods to produce designs that enhance the security of U.S. Federal Reserve notes (FRNs). This book presents the results of a systematic investigation of the trends in digital imaging and printing and how they enable emerging counterfeiting threats. It also provides the identification and analysis of new features of FRNs that could provide effective countermeasures to these threats and an overview of a requirements-driven development process that could be adapted to develop an advanced-generation currency.

The Flexible Electronics Opportunity - National Research Council (The National Academies Press, 2014)
Flexible electronics describes circuits that can bend and stretch, enabling significant versatility in applications and the prospect of low-cost manufacturing processes. They represent an important technological advance, in terms of their performance characteristics and potential range of applications, ranging from medical care, packaging, lighting and signage, consumer electronics and alternative energy (especially solar energy.) What these technologies have in common is a dependence on efficient manufacturing that currently requires improved technology, processes, tooling, and materials, as well as ongoing research. Seeking to capture the global market opportunity in flexible electronics, major U.S. competitors have initiated dedicated programs that are large in scope and supported with significant government funding to develop and acquire these new technologies, refine them, and ultimately manufacture them within their national borders. These national and regional investments are significantly larger than U.S. investment and more weighted toward later stage applied research and development. The Flexible Electronics Opportunity examines and compares selected innovation programs both foreign and domestic, and their potential to advance the production of flexible electronics technology in the United States. This report reviews the goals, concept, structure, operation, funding levels, and evaluation of foreign programs similar to major U.S. programs, e.g., innovation awards, S&T parks, and consortia. The report describes the transition of flexible electronics research into products and to makes recommendations to improve and to develop U.S. programs. Through an examination of the role of research consortia around the world to advance flexible electronics technology, the report makes recommendations for steps that the U.S. might consider to develop a robust industry in the United States. Significant U.S. expansion in the market for flexible electronics technologies is not likely to occur in the absence of mechanisms to address investment risks, the sharing of intellectual property, and the diverse technology requirements associated with developing and manufacturing flexible electronics technologies. The Flexible Electronics Opportunity makes recommendations for collaboration among industry, universities, and government to achieve the critical levels of investment and the acceleration of new technology development that are needed to catalyze a vibrant flexible electronics industry.

How Communities Can Use Risk Assessment Results: Making Ends Meet: A Summary of the June 3, 2010 Workshop of the Disasters Roundtable
During and after a disaster, text messages, tweets, Smartphone apps, and social networks, along with 24-hour cable news and other media, deliver relevant information to emergency responders, decision makers, and the general public. Participants in the workshop \

Assessment of Corrosion Education - National Research Council (The National Academies Press, 2009)
The threat from the degradation of materials in the engineered products that drive our economy, keep our citizenry healthy, and keep us safe from terrorism and belligerent threats has been well documented over the years. And yet little effort appears to have been made to apply the nation's engineering community to developing a better understanding of corrosion and the mitigation of its effects. The engineering workforce must have a solid understanding of the physical and chemical bases of corrosion, as well as an understanding of the engineering issues surrounding corrosion and corrosion abatement. Nonetheless, corrosion engineering is not a required course in the curriculum of most bachelor degree programs in MSE and related engineering fields, and in many programs, the subject is not even available. As a result, most bachelor-level graduates of materials- and design-related programs have an inadequate background in corrosion engineering principles and practices. To combat this problem, the book makes a number of short- and long-term recommendations to industry and government agencies, educational institutions, and communities to increase education and awareness, and ultimately give the incoming workforce the knowledge they need.